(untitled) (Journal of actual problems of jurisprudence, 2018)
This scientific article examines the written and oral forms of implementing the law language that represents a special code, that must possess a specialist lawyer. Good knowledge and a developed sense of language, the ability to use all of his wealth to those skilled in helping to achieve professional skills in the selected industries. Also, mastering the language features of legal texts, the possibility of a stylistic choice in the preparation of procedural documents, legal speech culture as an indicator of the general cultural level, a conscious attitude to the language – are a way for the high culture of thinking needed in a modern specialist construction law. Key words: law-linguistics, lexical features of law language, morphological changes, metaphors, irony, rhetoric questions and rhetoric exclamation.